2020
DOI: 10.1128/aem.02788-19
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Shotgun Analyses Reveal Complex Patterns of Intra- and Interspecific Variation in the Intestinal Microbiomes of Codfishes

Abstract: The relative importance of host-specific selection or environmental factors in determining the composition of the intestinal microbiome in wild vertebrates remains poorly understood. Here, we used metagenomic shotgun sequencing of individual specimens to compare the levels of intra- and interspecific variation of intestinal microbiome communities in two ecotypes (NEAC and NCC) of Atlantic cod (Gadus morhua) that have distinct behavior and habitats and three Gadidae species that occupy a range of ecological nic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 84 publications
(99 reference statements)
1
15
0
Order By: Relevance
“…Results suggest that species-specific selection, but also environmental factors comprise the major drivers of the intestinal community composition of the skipjack tuna. This intra-specific variability in the bacterial relative abundance has been also described for other fish species such as the grey mullet ( Mugil cephalus ) [ 70 ] and codfishes [ 71 ]. Tenericutes has been also identified as the dominant gut community in the southern bluefin tuna and king mackerel, while Firmicutes in Spanish mackerel [ 65 , 68 ], suggesting that both phyla are part of the microbiota of scombrids.…”
Section: Discussionsupporting
confidence: 57%
“…Results suggest that species-specific selection, but also environmental factors comprise the major drivers of the intestinal community composition of the skipjack tuna. This intra-specific variability in the bacterial relative abundance has been also described for other fish species such as the grey mullet ( Mugil cephalus ) [ 70 ] and codfishes [ 71 ]. Tenericutes has been also identified as the dominant gut community in the southern bluefin tuna and king mackerel, while Firmicutes in Spanish mackerel [ 65 , 68 ], suggesting that both phyla are part of the microbiota of scombrids.…”
Section: Discussionsupporting
confidence: 57%
“…However, given the strong documented interactions between host and gut microbiome [20] it appears unlikely that temperature alone would determine gut microbiome composition. Yet, temperature may modulate physiological effects on the gut microbiome [88]. Similarly, additional environmental factors would need to be considered in a coastal aquaculture setting, where the majority of the milkfish production is taking place in open cages or pens [3].…”
Section: Temperature Effects On the Milkfish Gut Microbiomementioning
confidence: 99%
“…On the other hand, unlike the pond water and sediment, the feed and gut are inherently linked by the high nutrient niche, which might impose a strong environmental selection of microbiota with functional traits linked to copiotroph (De Schryver and Vadstein, 2014 ; Troussellier et al ., 2017 ). Despite the evidences for the broad existence of core gut microbiota, accumulating studies had also showed substantial inter‐individual variation in the gut microbial communities for both cultured (Li, et al ., 2017 ; Perry, et al ., 2020 ) and wild‐captured fish species (Star, et al ., 2013 ; Egerton, et al ., 2018 ; Riiser, et al ., 2020 ). Several factors can contribute to such variability, including environmental filtering either by the host, for example variations between regions of the gastrointestinal tract, state of health and nutrition; or by the rearing environments such as diet (Wong, et al ., 2013 ; Clements, et al ., 2014 ).…”
Section: Introductionmentioning
confidence: 99%